1983
DOI: 10.1002/chin.198305206
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND ANTIFUNGAL ACTIVITY OF OXAZOLONES

Abstract: Das aus N‐Benzoylglycin (I) hergestellte Azlacton (II) wird mit Acetophenoniminen (III) zu α‐Methylbenzylidenoxazolonen (IV) kondensiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The reaction of benzalaniline and substituted benzalanilines with sulphene gives addition product 1,4-BT.1,4-Benzothiazine 5 , the heterocyclic compounds containing nitrogen and Sulphur in the six membered ring system. It has been reported to possess antifungal activity [6][7][8] . The Introduction of certain groups/atoms like -OH, -CH 3 , -OC 2 H 5 , -Cl etc.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of benzalaniline and substituted benzalanilines with sulphene gives addition product 1,4-BT.1,4-Benzothiazine 5 , the heterocyclic compounds containing nitrogen and Sulphur in the six membered ring system. It has been reported to possess antifungal activity [6][7][8] . The Introduction of certain groups/atoms like -OH, -CH 3 , -OC 2 H 5 , -Cl etc.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of electron releasing groups such as methoxy 4 , ethoxy 5 , hydoxy 6 etc. in the phenyl ring increases the activity of parent compound like Schiff bases and thiazolidinones.…”
Section: Introductionmentioning
confidence: 99%
“…in the phenyl ring increases the activity of parent compound like Schiff bases and thiazolidinones. The present investigation was carried out to study the effect of hydroxyl group in the ortho position of C-phenyl ring on the fungitoxicity of 1,2,4-oxadiazolines because it has been reported that the presence of OH group in ortho position of N-phenyl ring increases the activity of 1,2,4-oxadiazoline 7 manifold. The results of this study are being communicated in this paper.…”
Section: Introductionmentioning
confidence: 99%